2011
DOI: 10.1111/j.1552-3934.2011.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Weight Loss Program for Appalachian Kentucky Adults: A Formative Research Survey

Abstract: Although obesity rates are high in Appalachian Kentucky, few interventions have been developed for this population. The purpose of this study was to survey adults in the region about their needs and interest for a weight loss program. A telephone survey was conducted with 404 adults in Appalachian Kentucky. Sixty‐nine percent (69%) of respondents were overweight or obese. Nearly half (48%) of respondents reported a diagnosis of a chronic health condition. The most frequently mentioned barriers to weight loss w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…The dimensional analysis included the following steps: (a) identify conditions, (b) identify the dimensions and sub dimensions of obesity related to Appalachian women, (c), identify the perspectives of women living in Appalachia in regard to obesity, (d) 2010; Schoenberg et al, 2008;Serrano, Leiferman, & Dauber, 2007;Webber & Quintiliani, 2011;Vona-Davis et al, 2008). It is also well documented that Appalachian women have less education, household income, and access to healthcare than women living outside the Appalachian region (Coyne et al, 2006;Ramsey & Glenn, 2002;Serrano et al, 2007;Tessaro, Rye, Parker, Mangone, & McCrone, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dimensional analysis included the following steps: (a) identify conditions, (b) identify the dimensions and sub dimensions of obesity related to Appalachian women, (c), identify the perspectives of women living in Appalachia in regard to obesity, (d) 2010; Schoenberg et al, 2008;Serrano, Leiferman, & Dauber, 2007;Webber & Quintiliani, 2011;Vona-Davis et al, 2008). It is also well documented that Appalachian women have less education, household income, and access to healthcare than women living outside the Appalachian region (Coyne et al, 2006;Ramsey & Glenn, 2002;Serrano et al, 2007;Tessaro, Rye, Parker, Mangone, & McCrone, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Women living in the Appalachian region earn less income and have poorer health outcomes than women in the US as a whole (Amonkar & Madhavan, 2002;Pearson et al, 2010;Schoenberg et al, 2008;Serrano et al, 2007;Webber & Quintiliani, 2011;Vona-Davis et al, 2008). Several studies have found that Appalachian women earn an average annual income of less than $20,000 (Ramsey & Glenn, 2002;Rye, Rye, Tessaro, & Coffindaffer, 2009;Schoenberg, Hatcher, & Dignan, 2008;Schoenberg, Hopenhayn, Christian, Knight, & Rubio, 2005;Tessaro et al, 2007).…”
Section: Dimension: Povertymentioning
confidence: 99%
See 2 more Smart Citations
“…Customizing interventions to meet the needs of specific populations may increase likelihood of success (Webber & Quintiliani, 2011). Though this study was limited to a small sample in one county, recommendations based on the findings are also supported in the literature.…”
Section: Implications For Research and Practicementioning
confidence: 64%